2013
DOI: 10.1155/2013/731609
|View full text |Cite
|
Sign up to set email alerts
|

Association between Angiotensin II Type 1 Receptor Polymorphism and Sudden Cardiac Death in Myocardial Infarction

Abstract: Objective. The renin-angiotensin system is involved in the pathogenesis of coronary artery disease and myocardial infarction (MI). Angiotensin II (Ang II) has many adverse effects such as vasoconstriction and vascular remodeling, and these actions are mediated by the angiotensin II type 1 receptor (AT1R). Patients and Methods. A total of 1376 patients were recruited from January 2010 to April 2012. The study group consisted of 749 patients with ACS (317 females and 432 males) and of 627 healthy controls. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
1
11
0
1
Order By: Relevance
“…Kruzliak P et al . found that the CC genotype is associated with a higher risk of three-vessel stenosis and also a higher proportion of left anterior descending (LAD) artery infarction [ 9 ]. In contrast, when comparing the CC genotype with AC and AA genotypes in AMI patients, Araújo MA et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kruzliak P et al . found that the CC genotype is associated with a higher risk of three-vessel stenosis and also a higher proportion of left anterior descending (LAD) artery infarction [ 9 ]. In contrast, when comparing the CC genotype with AC and AA genotypes in AMI patients, Araújo MA et al .…”
Section: Introductionmentioning
confidence: 99%
“…did not detect a relationship between the AGTR1 A1166C variant and coronary artery injuries [ 10 ]. However, AGTR1 A1166C has been revealed in several studies to be a prognostic factor for mortality in patients with AMI [ 9 , 11 , 12 ], although other studies have not found any predictive value [ 13 , 14 ]. Given the lack of data and the conflicting results between various studies, we conducted this study to investigate the effect of the AGTR1 A1166C genetic variant on coronary artery lesion characteristics and mortality in Vietnamese patients with AMI.…”
Section: Introductionmentioning
confidence: 99%
“…In human studies; however, it is generally accepted that ACE inhibitors can reduce the risk of MI whereas it is controversial whether Ang II receptor blockers are beneficial or detrimental to MI 13-15 . In spite of this, genetic polymorphisms of the AT1R gene as well as the ACE gene are associated with a high risk for coronary events 16-19 . It is well known that Ang II infusion leads to the enhancement of atherosclerosis and the formation of aortic aneurysms in hyperlipidemic mice 20, 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of VEGFA were found to be associated with the risk of CHD [15]. Angiotensin II type 1 receptor (AGTR1) encodes the type 1 receptor mediating the major cardiovascular effects of angiotensin II (Ang II) [16], which has many adverse effects such as vasoconstriction and vascular remodeling [17]. Angiotensin I converting enzyme (ACE) also encodes the same angiotensin converting enzyme.…”
Section: Introductionmentioning
confidence: 99%